2002
DOI: 10.1159/000048995
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Actin Cytoskeleton of Cardiac Capillary Endothelial Cells during Ischaemia and Reperfusion: The Effect of Phalloidin on Cell Shape

Abstract: A reduction in capillary dimensions has been demonstrated in postischaemic reperfusion in the heart. The aim of this study was to demonstrate that in ischaemia and ischaemia followed by reperfusion, the change in shape of the constituent endothelial cells can be inhibited by phalloidin which stabilises the actin microfilament system. Isolated, perfused rat hearts were made globally ischaemic both with and without reperfusion and in the presence or absence of phalloidin. Changes in ischaemic endothelial cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…It is reported that high levels of MMPs cause cells to become detached from the extracellular matrix, directing them toward apoptosis (Woessner, 1991;Frisch & Francis, 1994). Reperfusion was also shown to result in structural and biochemical changes in endothelial cells leading to damaged endothelium (Glyn and Ward, 2002). The present in vitro results, demonstrating for the first time H/R-induced MMP-2 secretion in HUVE cells, are in accordance with in vivo studies performed on ischemia/reperfusion injury and MMP activities (Zhang et al, 2002;Lalu et al, 2005, Catalyurek et al, 2008Lu et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…It is reported that high levels of MMPs cause cells to become detached from the extracellular matrix, directing them toward apoptosis (Woessner, 1991;Frisch & Francis, 1994). Reperfusion was also shown to result in structural and biochemical changes in endothelial cells leading to damaged endothelium (Glyn and Ward, 2002). The present in vitro results, demonstrating for the first time H/R-induced MMP-2 secretion in HUVE cells, are in accordance with in vivo studies performed on ischemia/reperfusion injury and MMP activities (Zhang et al, 2002;Lalu et al, 2005, Catalyurek et al, 2008Lu et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…However, indirect evidence using vasoactive chemicals to induce reorganization of the endothelial microfilament system also suggests that endothelial cells play a role in capillary constriction in a number of vascular beds. 35 Although our data show that isolated pulmonary (but not aortic) endothelial cells actively contract in response to hypoxia, the integrated subunit of intraacinar arteries under investigation contains both endothelium and a small component of discontinuous smooth muscle, and, as such, either or both cell types could contribute to vasomotor tone.…”
Section: Discussionmentioning
confidence: 58%
“…However, indirect evidence using vasoactive chemicals to induce reorganization of the endothelial microfilament system also suggests that endothelial cells play a role in capillary constriction in a number of vascular beds. 35 Although our data show that isolated pulmonary (but not aortic) endothelial cells actively contract in response to hypoxia, the integrated subunit of intraacinar arteries under investigation contains both endothelium and a small component of discontinuous smooth muscle, and, as such, either or both cell types could contribute to vasomotor tone.It is now apparent that: (1) S-nitrosation of zinc sulfur clusters is an important component of NO signaling; and (2) MT is a critical link between NO and intracellular zinc homeostasis. 7 Our present data support the contention that zinc thiolate signaling is a component of acute hypoxia mediated NO biosynthesis and that this pathway may contribute to hypoxia-induced vasoconstriction within the pulmonary microcirculation.…”
mentioning
confidence: 58%
“…While the heart and circulation of the zebrafish embryo are functional from 1 dpf, expression of embryonic smooth muscle cell markers is relatively weak and discontinuous throughout the length of the dorsal aorta even at 5 dpf [35], as we confirmed in our model using transmission electron microscopy (TEM, Figure S2 ). Vascular endothelium contains all the molecular machinery required to generate contractile force via the actomyosin motor, and has been shown to play a role in capillary constriction in a number of vascular beds in other vertebrate models [36], [37] , [38]. Furthermore, endothelial cells in early stage zebrafish embryos have been shown to produce vasoconstrictive agents including prostacyclin [11]; and nitric oxide (NO) has been shown to modulate vascular tone early in development when both nervous control and smooth muscle cells are limited or lacking [39], [40].…”
Section: Discussionmentioning
confidence: 99%